Peculiarities of Legal Regulation of Non-Discrimination on Gender Basis while Being Employed (Law and Safety, 2021)
The Constitution of Ukraine enshrines and guarantees the right to labor as an opportunity to earn a living by work that a person freely chooses or agrees to. However, the current conditions indicate that the consolidation and guarantee of everyone’s right to labor is not an unconditional evidence of its inviolability, the absence of unjustified restrictions and obstacles to its realization. One of such obstacles to the realization of this right is gender discrimination, which violates the balance of male and female labor at the labor market and creates an imbalance in the harmonious development of labor and closely related relations. In this regard, the author has emphasized the importance of the existence of a wide range of effective legal principles in the national labor legislation for non-discrimination while employment, in particular on the grounds of sex, as well as an effective mechanism for their realization.It has been clarified that the legal regulation of non-discrimination on the grounds of sex while employment is the legal regulation of labor and closely related relations through legal means in order to achieve gender parity, prevention of any manifestations of gender discrimination in the realization of the right to labor by each person and citizen.It has been established that the current state of the development of legislative provisions of Ukraine in the field of employment implies the existence of a certain range of legal principles regulating the prevention of discrimination on the grounds of sex while being employed. The emphasis has been placed on the analysis of certain legal principles of non-discrimination, the effect of which extends to the stage of job search and acquaintance with current vacancies at the labor market. Their legal content has been analyzed and suggestions for their semantic improvement have been provided.It has been determined that an unjustified refusal to be hired should be considered a refusal that is devoid of any motivation or when an employer refuses a candidate for reasons other than his professional and business qualities, or does not take into account a number of special requirements provided by the current legislation.The author has emphasized on the need to create legal conditions for the harmonious combination of the interests of an employee and an employer, which can assist in preventing discrimination and allowштп each party to labor and closely related relations to achieve the desired result in realizing their labor rights and interests.
Keywords: discrimination; scope of labor; legal regulation; gender features; employment; right to labor.